Association of alcohol consumption with sleep disturbance among adolescents in China: a cross-sectional analysis - Yanhong Liu; Lei Zhang; Meng Yao; Yanrou Li; Kang Cao; Yongzheng Deng (Frontiers in Public Health)
BackgroundEvidence suggests a potential association between alcohol consumption and sleep quality. However, knowledge of this association among adolescents in China is limited. Thus, this study aims to investigate the association between alcohol consumption and sleep quality in a group of adolescents in China.MethodsA cross-sectional survey was conducted in Shenzhen, Guangdong Province in China from October 2021 to December 2021. Alcohol consumption refers to drinking more than half a bottle/a can of beer, a small cup of white wine/foreign wine and a glass of wine/rice wine/fruit wine/highland wine at a time in the past year. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) with a cutoff >5 indicating sleep disturbance. Multivariable logistic regression models were utilized to estimate the association.ResultsA total of 2,505 adolescents were included in the analysis. Among them, the mean age was 14.36 years (SD 1.74); 58.08% were male, and 41.92% were female. The overall drinking rate was 26.07%, and the median score of PSQI was 5. The interquartile distance of the PSQI global score was 4. Multivariable logistic regression illustrated that alcohol consumption exhibited positive significant associations with poor PSQI scores (OR = 1.89, 95% CI: 1.52–2.35) compared with good scores.ConclusionAlcohol consumption is associated with poor sleep quality in adolescents in China accounting for socioeconomic contexts and psychosocial stressors. The findings underscore the public health urgency of addressing alcohol drinking behaviors to mitigate sleep disturbances in adolescents. Further studies need to be performed to explore the causality between alcohol consumption and sleep quality in adolescents. Frequency and dosage of alcohol consumption need to be considered to explore dose–response relationships.